2022
DOI: 10.1186/s12888-022-04203-8
|View full text |Cite
|
Sign up to set email alerts
|

Further validation of the Cognitive Biases Questionnaire for psychosis

Abstract: Background Cognitive biases are recognized as important treatment targets for reducing symptoms associated with severe mental disorders. Although cognitive biases have been linked to symptoms in most studies, few studies have looked at such biases transdiagnostically. The Cognitive Bias Questionnaire for psychosis (CBQp) is a self-reported questionnaire that assesses cognitive biases amongst individuals with a psychotic disorder, as well as individuals with other severe mental disorders. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Several studies reported means for several diagnoses combined together into broader categories, for example, anxiety disorders (De Cort et al, 2008;Lichtenstein-Vidne et al, 2017;Neng and Weck, 2015), depressive disorders (Duddu et al, 2003;Wittorf et al, 2012), and schizophrenia-spectrum disorders (Krkovic et al, 2023;Samson et al, 2022;Wittorf et al, 2012;Zhu et al, 2020), thus limiting the feasible categories for network meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several studies reported means for several diagnoses combined together into broader categories, for example, anxiety disorders (De Cort et al, 2008;Lichtenstein-Vidne et al, 2017;Neng and Weck, 2015), depressive disorders (Duddu et al, 2003;Wittorf et al, 2012), and schizophrenia-spectrum disorders (Krkovic et al, 2023;Samson et al, 2022;Wittorf et al, 2012;Zhu et al, 2020), thus limiting the feasible categories for network meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%